A comparative study of methods for determining carbonate content in marine and terrestrial sediments. (June 2020) - Fu, Hanjing; Jian, Xing; Zhang, Wei; Shang, Fei
Abstract: Carbonate can be produced in a variety of environments on the Earth's surface, such as shallow seas and deep oceans, continental lakes, soils and subsurface aquifers. The carbonate content of sediments is an important proxy in paleoceanography and paleoclimatology and is often used to reconstruct paleoenvironmental evolution of the earth. Many methods have been reported to measure the content of carbonate in sediments, but how those methods perform (e.g. degree of accuracy and precision, error-induced factors, operability, cost and time) remains understudied. Here, we employ three widely-used non-instrumental methods, including acid-base titration, gasometric method, and loss on ignition (LOI) based on muffle combustion, together with X-ray diffraction for mineral phase analysis, to compare the carbonate content data of sediments from deep ocean (water depths from 1218 m to 6147 m) of the western Pacific and Cenozoic sedimentary rocks from the Qaidam basin, northern Tibetan Plateau. The results show that data accuracies of most methods are closely related to mineral compositions in sediments (e.g. carbonate species and clay mineral contents) and analytical operations. Non-instrumental methods generally demonstrate low precisions (avg. RSD of 3.36%) in determining sediments with low carbonate contents (<20% wt). Among the three approaches, the LOI method performs best with relatively high accuracy (avg. recovery of 99.79%) and precision (avg. RSD of 0.27%) when determining carbonate-rich sediments with simple mineral compositions (e.g. only calcium carbonate). Although dehydroxylation of clay minerals might influence the results, the LOI method has advantages of ease of operation, short time-consuming and convenience for batch determinations. Acid-base titration and gasometric methods indicate moderate precisions (avg. RSD of 1.73% and 2.76%, respectively) and accuracies (108.64% and 101.85%, respectively) with quick measurement, affordable cost and requirement of high-quality manual operation. Additionally, we suggest that the analytical procedures, such as sample size, reaction time, temperature, reagent concentration, weighing error, endpoint judgement of titration can influence the data quality. This study provides significant selecting principles for carbonate determination methods and would be beneficial to carbonate-related study in various aspects of geosciences. Highlights: Carbonate determination accuracy is closely related to sediment compositions. Non-instrument methods perform well for analyzing sediments with >20% wt carbonate. Rigorous analytical procedures are important to non-instrument methods. LOI method is most recommended in this study for best precision and accuracy.